2021
DOI: 10.1029/2021jf006096
|View full text |Cite
|
Sign up to set email alerts
|

The Transport History of Alluvial Fan Sediment Inferred From Multiple Geochronometers

Abstract: In this article we explore the use of the in situ produced cosmogenic nuclides beryllium-10 ( 10 Be) and carbon-14 ( 14 C) in conjunction with post-infrared infrared stimulated luminescence (p-IR IRSL) measurements from a Holocene alluvial fan in Southern California for both chronometric purposes and to understand sediment storage and mobilization history prior to delivery to alluvial fans. This is important because alluvial fan deposits are recognized as potential archives of past climatic and tectonic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Although several studies have shown near‐complete bleaching in downstream reaches of major rivers (Chamberlain et al., 2018; Wallinga, 2002), heterogeneous bleaching of quartz and feldspar is common for smaller systems and upstream reaches (Bonnet et al., 2019; Chamberlain & Wallinga, 2019; Wallinga, 2002). Such heterogeneous bleaching may be due to attenuated bleaching efficiency in turbid flow (Ditlefsen, 1992), luminescence signal bleachability (Kars et al., 2014), fast erosion rates (Bonnet et al., 2019), alongstream supply of unbleached grains (Guyez, Bonnet, Reimann, Carretier, & Wallinga, 2022), or dose regeneration due to temporary storage in floodplains (Goehring et al., 2021). The few studies that have investigated D e variations of modern sediment alongstream (Gray et al., 2018; Guyez, Bonnet, Reimann, Carretier, & Wallinga, 2022; McGuire and Rhodes, 2015a, 2015b; Stokes et al., 2001) document longitudinal decreases in mean D e , interpreted as the signature of a progressive D e reduction of the sediment mix due to cumulative bleaching.…”
Section: Background: Luminescence Of Fluvial Sedimentsmentioning
confidence: 99%
“…Although several studies have shown near‐complete bleaching in downstream reaches of major rivers (Chamberlain et al., 2018; Wallinga, 2002), heterogeneous bleaching of quartz and feldspar is common for smaller systems and upstream reaches (Bonnet et al., 2019; Chamberlain & Wallinga, 2019; Wallinga, 2002). Such heterogeneous bleaching may be due to attenuated bleaching efficiency in turbid flow (Ditlefsen, 1992), luminescence signal bleachability (Kars et al., 2014), fast erosion rates (Bonnet et al., 2019), alongstream supply of unbleached grains (Guyez, Bonnet, Reimann, Carretier, & Wallinga, 2022), or dose regeneration due to temporary storage in floodplains (Goehring et al., 2021). The few studies that have investigated D e variations of modern sediment alongstream (Gray et al., 2018; Guyez, Bonnet, Reimann, Carretier, & Wallinga, 2022; McGuire and Rhodes, 2015a, 2015b; Stokes et al., 2001) document longitudinal decreases in mean D e , interpreted as the signature of a progressive D e reduction of the sediment mix due to cumulative bleaching.…”
Section: Background: Luminescence Of Fluvial Sedimentsmentioning
confidence: 99%